Hubungan Kepuasan Kerja dengan Perilaku Caring Perawat selama Pandemi Covid-19 di Ruang Rawat Inap RSU dr. Koesnadi Bondowoso - Fauzatul Walidanik; Anisah Ardiana; Nurfika Asmaningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
As one of the front lines in dealing with the COVID-19 pandemic, nurses immediately face situations that cause psychological symptoms such as work stress. Work stress can be caused by several factors, including job satisfaction with the job, salary, co-workers, supervision, and promotion opportunities. Job satisfaction is not a protective factor in the formation of nurse-caring behavior. However, other factors include work involvement, nurses' psychology, work stress, and work motivation. If the nurse experiences work stress, it will result in the nurse's caring behavior being less than optimal. This study aims to analyze the relationship between job satisfaction and the caring behavior of nurses during the COVID-19 pandemic in the inpatient room at RSU dr. H. Koesnadi Bondowoso. The design of this study is a correlation study with a cross-sectional approach. The research sample used a purposive sampling of 104 nurses in non-COVID-19 inpatient rooms. This study was analyzed using the Spearman test. Spearman test results show the value of value = 0.029 (α <0.05) with a correlation coefficient of -0.214. Higher job satisfaction will cause nurses' caring behavior to be less than optimal, which is caused by several other factors of job satisfaction, such as work involvement, nurse psychology, work stress, and work motivation.